Spiritual and Cultural Significance of Religious Prose - I.V., Rodina (RA Journal of Applied Research, 2023)
The article systematizes the key criteria of religious prose as a directional system in modern Russian literature. The emphasis on the consideration of the concept–forming complex of problems “God–being–man” allows us to identify the specifics of the evolution of the spiritual and cultural consciousness of the “crisis” era of the twentieth century. An analysis of the range of issues related to the mystery of human existence correlates with the concepts of the best representatives of world culture, science, and literature.